Inheritance Distribution Dynamics of Indigenous Peoples: Studies in Society Seberang Jambi City - Yuliatin Yuliatin; Yudi Armansyah (Proceedings of Annual Conference for Muslim Scholars, 2017)
Customs and religion (Islam) is a braid that can not be separated from each other. With emphasis on synergy between religion and customs, as is customary that bersendikan syarak and syarak that bersendikan Kitabullah, syarak mengato, traditional wear. Similarly in the division of the estate. Where, in general in Indonesia are still frequent mixing between customary law and Islamic law in the determination and distribution of the estate. This article attempts to explore the dynamics of the division of an estate that occurs in Indigenous communities Seberang Kota Jambi. Across society is a society that still maintain the socio-cultural traditions and customs of the Jambi. This is evident from the division of the estate are still using Seberang customary law, although in practice they insert the values of Islam. However, integration between Islamic and Customary law should be examined in more depth. How the actual dynamics of the division of inheritance in Seberang community and factors that encourage people Seberang Kota Jambi carry out the division of the estate with Islamic law and customary law.